1990
DOI: 10.1021/bi00498a015
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-17, proton, and deuterium electron nuclear double resonance characterization of solvent, substrate, and inhibitor binding to the iron-sulfur [4Fe-4S]+ cluster of aconitase

Abstract: 17O electron nuclear double resonance (ENDOR) studies at X-band (9-GHz) and Q-band (35-GHz) microwave frequencies reveal that the [4Fe-4S]+ cluster of substrate-free aconitase [citrate (isocitrate) hydro-lyase, EC 4.2.1.3] binds solvent, HxO (x = 1, 2). Previous 17O ENDOR studies [Telser et al. (1986) J. Biol. Chem. 261, 4840-4846] had disclosed that Hx17O binds to the enzyme-substrate complex and also to complexes of enzyme with the substrate analogues trans-aconitate and nitroisocitrate (1-hydroxy-2-nitro-1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
64
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 16 publications
7
64
0
Order By: Relevance
“…Mossbauer spectroscopy also indicated that the ligand environment of Fe, is significantly altered upon the addition of substrate (Emptage et al, 1983b). These findings are consistent with the indication from "0-ENDOR studies (Werst et al, 1990a) that substrate binds directly to the cluster, through Fe,, in this partially active form of the enzyme. Crystallographic studies have demonstrated that upon the addition of substrate (citrate, cis-aconitate or isocitrate) to the oxidised [4Fe-4SI2+ form Fe, forms an isocitrate complex with the substrate molecule binding via the Ca-hydroxyl oxygen atom and a Ca-carboxylate oxygen (denoted OHA and OA2, respectively;Lauble et al, 1992).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Mossbauer spectroscopy also indicated that the ligand environment of Fe, is significantly altered upon the addition of substrate (Emptage et al, 1983b). These findings are consistent with the indication from "0-ENDOR studies (Werst et al, 1990a) that substrate binds directly to the cluster, through Fe,, in this partially active form of the enzyme. Crystallographic studies have demonstrated that upon the addition of substrate (citrate, cis-aconitate or isocitrate) to the oxidised [4Fe-4SI2+ form Fe, forms an isocitrate complex with the substrate molecule binding via the Ca-hydroxyl oxygen atom and a Ca-carboxylate oxygen (denoted OHA and OA2, respectively;Lauble et al, 1992).…”
supporting
confidence: 91%
“…X-ray crystallography (Robbins and Stout, 1989) protein. Mossbauer (Kent et al, 1982; Emptage et al, 1983b) and electron-nuclear double resonance (ENDOR; Telser et al, 1986;Kennedy et al, 1987;Werst et al, 1990a) spectroscopic studies have revealed that Fe;, has, in addition to three inorganic sulphur bridging ligands, a hydroxyl anion ligand which persists but becomes protonated upon binding of the C2 carboxylate anion of cis-aconitate to Fe,. The inequivalence of the iron sites in the cluster has been highlighted by 57Fe-ENDOR and "S-ENDOR and it has been further shown that the nuclei of two of the inorganic sulphide bridging ligands are considerably more strongly coupled to the paramagnetic electron density in the reduced [4Fe-4S] ' cluster than are those of the other two (Werst et al, 1990b).…”
mentioning
confidence: 99%
“…Aconitase was inactivated in extracts exposed to 1200 ppm NO ⅐ in N 2 (Fig. 5, line 2), and the virtual substrates fluorocitrate, trans-aconitate, and tricarballylate (29,40,41) completely blocked this inactivation (Fig. 5, compare lines 3-5 with lines 1 and 2).…”
Section: Aconitase Is Sensitive To No ⅐ In E Coli In the Absence Of mentioning
confidence: 92%
“…Citrate 3-OH oxygen binding to Fe a may decrease the NO ⅐ reactivity, or alternatively, cis-aconitate may increase the reactivity by altering the ligand field of Fe a . The citrate hydroxyl oxygen does alter the Fe a in the mitochondrial aconitase as indicated by ENDOR (electron nuclear double resonance), EPR, and Möss-bauer spectroscopy (40,41,44). However, the ability of the hydroxylless trans-aconitate and tricarballylate to protect aconitase equally with that of the hydroxyl-containing inhibitor fluorocitrate (Fig.…”
Section: Figmentioning
confidence: 98%
“…A key mechanistic question regarding this family is the role of the cluster in this process. In particular, the [4Fe-4S] cluster of enzymes in the Fe-S͞ AdoMet family has a ''unique'' iron site that is not coordinated to the enzyme by a cysteinyl sulfur; does this Fe have a catalytic function, as is the case for aconitase (25)?…”
Section: Dual Role Of the Catalytically Active [4fe-4s] ؉mentioning
confidence: 99%